PENGARUH VALUE ADDED INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DAN NILAI PASAR PERUSAHAAN KHUSUSNYA DI INDUSTRI PERDAGANGAN JASA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008 – 2013 - Sirapanji Olivia; SAARCE ELSYE HATANE (Business Accounting Review, 2015)
This study aimed to examine the affect of value added intellectual capital with financial performance and market value of the company. The sample used in this study were 38 companies in the field of trade in services that are consistently listed in the Indonesian Stock Exchange in 2008-2013 . The hypothesis in this study tested by using multiple linear regression statistical test . VAIC measured by using the concept of Pulic (2005 ) then linked to financial performance ( ROA , ROE ) and the company's market value ( Tobin 's Q ) . The results of this study indicated that not all components of VAIC colud have positive and significant influence on profitability and market value of the company . HCE only can affect the market value of the company , while the CEE was only able to affect the profitability of the company. While the VAIC components that consistent by affecting profitability and market value was structural capital efficiency ( SCE )